Implementing an institution-wide quality improvement policy to ensure appropriate use of continuous cardiac monitoring: a mixed-methods retrospective data analysis and direct observation study. Issue 10 (13th November 2015) - Rayo, Michael F; Mansfield, Jerry; Eiferman, Daniel; Mignery, Traci; White, Susan; Moffatt-Bruce, Susan D
Abstract : Background: Hospitals have been slow to adopt guidelines from the American Heart Association (AHA) limiting the use of continuous cardiac monitoring for fear of missing important patient cardiac events. A new continuous cardiac monitoring policy was implemented at a tertiary-care hospital seeking to monitor only those patients who were clinically indicated and decrease the number of false alarms in order to improve overall alarm response. Methods: Leadership support was secured, a cross-functional alarm management task force was created, and a system-wide policy was developed based on current AHA guidelines. Process measures, including cardiac monitoring rate, monitored transport rate, emergency department (ED) boarding rate and the percentage of false, unnecessary and true alarms, were measured to determine the policy's impact on patient care. Outcome measures, including length of stay and mortality rate, were measured to determine the impact on patient outcomes. Results: Cardiac monitoring rate decreased 53.2% (0.535 to 0.251 per patient day, p<0.001), monitored transport rate decreased 15.5% (0.216 to 0.182 per patient day, p<0.001), ED patient boarding rate decreased 36.6% (5.5% to 3.5% of ED patients, p<0.001) and the percentage of false alarms decreased (18.8% to 9.6%, p<0.001). Neither the length of stay nor mortality changed significantly after the policy was implemented. Conclusions: The observed improvements in process measures coupled with no adverse effects to patient outcomes suggest that the overall system became more resilient to current and emerging demands. This study indicates that when collaboration across a diverse team is coupled with strong leadership support, policies and procedures such as this one can improve clinical practice and patient care.